2013
DOI: 10.1504/ijsse.2013.053490
|View full text |Cite
|
Sign up to set email alerts
|

A framework to address the impact of system of systems integration using commercially off the shelf (COTS) technology

Abstract: For systems engineering, systems integration (SI) establishes linkages between hardware (HW), software (SW), products, services, processes and humans. Over the last decade the world of systems development has evolved rapidly particularly in the use of commercial-off-the-shelf (COTS) products as elements of larger systems. The growing trend toward COTS-based systems (CBS) architectures is based on modular components available within the market. This trend has presented various challenges for systems engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Keeping up with newer versions of every COTS component is often cumbersome, expensive, and infeasible for developing and maintaining CPS systems. Therefore, a major challenging issue is to strategically refresh COTS versions 53 . The refresh and renewal process for COTS needs to be defined a priori and managed so that COTS updates can be synchronized with each other and the organization's release and business cycles 23 .…”
Section: A Cots Td Taxonomy For the Engineering Of Complex Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping up with newer versions of every COTS component is often cumbersome, expensive, and infeasible for developing and maintaining CPS systems. Therefore, a major challenging issue is to strategically refresh COTS versions 53 . The refresh and renewal process for COTS needs to be defined a priori and managed so that COTS updates can be synchronized with each other and the organization's release and business cycles 23 .…”
Section: A Cots Td Taxonomy For the Engineering Of Complex Systemsmentioning
confidence: 99%
“…Therefore, a major challenging issue is to strategically refresh COTS versions. 53 The refresh and renewal process for COTS needs to be defined a priori and managed so that COTS updates can be synchronized with each other and the organization's release and business cycles. 23 If the decision is to skip certain newer COTS versions, potential version conflict risks due to complicated inter-dependencies would be introduced, and this may eventually lead to out of sync build dependencies, 54 and/or COTS obsolescence.…”
Section: Functionalitymentioning
confidence: 99%
“…Basu et al (2007) identified risks of suppliers in financial trouble, supply side capacity constraints, and common supplier dependency risks, while Silver and Daly (2007) identified liabilities arising from outsourcing of legal and law-related services. Another area of SCR concern is using commercial-off-the-shelf technologies from suppliers, which are integrated into larger systems (VanLeer and Jain, 2013).…”
Section: Suppliersmentioning
confidence: 99%